Changing indications for a total pancreatectomy: perspectives over a quarter of a century. Issue 5 (May 2015) - Almond, Max; Roberts, Keith J.; Hodson, James; Sutcliffe, Robert; Marudanayagam, Ravi; Isaac, John; Muiesan, Paolo; Mirza, Darius
Abstract: Introduction: The indications for a total pancreatectomy (TP), its perioperative management, provision of pancreatic surgical services and medical treatment of the inherent exo and endocrine deficient states have all changed considerably over recent decades. The effects of these upon the incidence, indications for and outcomes of TP are unclear. Patients undergoing TP at a single institution over a quarter of a century were reviewed to try to address these issues. Methods: Data on patients who underwent elective (el) and emergency TP (emTP) between 1987 and 2013 were reviewed. Patient demographics, indications, intraoperative details, perioperative management and longterm outcomes were analysed. Absolute numbers of TP were reported relative to partial pancreatectomy rates. Results: In total, 136 patients underwent TP [98 (72.1%) elTP; 38 (27.9%) emTP]. There was a significant change in indication for elTP with it increasingly performed for (an intraductal papillary mucinous neoplasm (IPMN) and renal cell metastases whereas there was a decrease in the number of elTP performed for chronic pancreatitis ( P = 0.025). The relative rates of elTP, however, did not change significantly across the study period ( P = 0.225). The median length of stay after elTP decreased from 19 days pre1997 to 12 days post1997 ( P = 0.009). The relative use of emTP declined by 0.28 percentage points per year [ P = 0.018; 95% confidence interval (CI): 0.04–0.41]. Conclusions: The indications for elTP have changed; it is being performed more frequently although the proportion relative to other pancreatic resections has not changed. A decrease in the rate of emTP is likely to reflect improved perioperative management of a pancreatic fistula and its complications after a pancreaticoduodenectomy.